Do oil exports fuel defense spending? - Chun, Clayton K. S. (Strategic Studies Institute, U.S. Army War College, 2010)
Many national security analysts have viewed oil-exporting countries with some trepidation. Although these exporting nations supply a vital energy source to the United States and her allies, it comes at a price. A great wealth transfer occurs in this process from oil importers to exporters. In some cases, oil importers face economic woes if energy prices rise sharply. Additionally, some critics might argue that oil exporters now have the financial wherewithal to acquire a military capability that could threaten neighbors or create intra-regional instability with global implications. This monograph explores the impact that oil revenue had on the national defense spending of five oil exporting countries. Despite periods of falling oil revenues, these countries typically did not lower defense spending.--